2003
DOI: 10.1212/01.wnl.0000044154.92143.dc
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of brain activation during trial-and-error sequence learning in early PD

Abstract: Mildly affected patients with PD demonstrated only modest impairment of learning during the first 30 seconds of the task and performed equivalently with controls thereafter. However, the mechanism by which they achieved equiperformance involved considerable changes in brain function. The PD group had to activate four times as much neural tissue as the controls, including recruiting brain from homologous cortical regions and bilateral lateral cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 36 publications
2
85
0
Order By: Relevance
“…Functional neuroimaging studies have repeatedly shown changes in activation in motor and premotor areas in PD during performance of motor tasks, particularly in the supplementary motor area. [23][24][25][26][27][28][29] Dysfunction of medial frontal areas, which presumably results from altered basal ganglia interactions due to nigrostriatal dopaminergic loss, plays a role in impaired motor performance (ie, hypokinesia). 1,30 This type of functional cortical deafferentation is supported by brain imaging studies showing diminished regional blood flow in the supplementary motor area 24 and the prefrontal region.…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging studies have repeatedly shown changes in activation in motor and premotor areas in PD during performance of motor tasks, particularly in the supplementary motor area. [23][24][25][26][27][28][29] Dysfunction of medial frontal areas, which presumably results from altered basal ganglia interactions due to nigrostriatal dopaminergic loss, plays a role in impaired motor performance (ie, hypokinesia). 1,30 This type of functional cortical deafferentation is supported by brain imaging studies showing diminished regional blood flow in the supplementary motor area 24 and the prefrontal region.…”
Section: Discussionmentioning
confidence: 99%
“…Vermis activation also occurs during reward tasks in Parkinson's and in attention deficit hyperactivity disorder patients, but not in comparison subjects (Ernst et al, 2003;Goerendt et al, 2004;Kunig et al, 2000). In addition, increased cerebellar (and vermis) activation occur to support working memory function in frontotemporal dementia, Parkinson's Disease, and schizophrenia, (Mentis et al, 2003;Meyer-Lindenberg et al, 2001;Rombouts et al, 2003). Thus, several domains of frontal lobe function pertinent to addiction-related behaviors appear to be supported by cerebellum and vermis.…”
Section: Cerebellar Connectivity To Dopamine Circuitrymentioning
confidence: 95%
“…The involvement of the cerebellum and dentate nuclei in both the PDRP and PDCP is compatible with the presence of distinct motor and non-motor efferent channels from the dentate nuclei to the striatum and cerebral cortex (cf., Dum et al, 2002;Hoshi et al, 2005). The latter may be particularly critical in the performance of complex tasks, as demonstrated by increased cerebellar-prefrontal activity in PD patients during trial-and-error sequence learning (Mentis et al, 2003). By contrast, the prominent increases in basal ganglia-thalamic activity that are characteristic of the PDRP (Moeller et al, 1999;cf., Carbon et al, 2003a) did not contribute to the PDCP spatial topography.…”
Section: Anatomical/functional Basis For the Pdcp Topographymentioning
confidence: 99%